2013
DOI: 10.5603/cj.2013.0045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ASA dose doubling versus switching to clopidogrel on plasma inflammatory markers concentration in patients with type 2 diabetes and high platelet reactivity: The AVOCADO study

Abstract: Background: The aim of the study was to compare the effects of 2 strategies of antiplatelet treatment (i.e., 150 mg ASA vs. 75 mg clpoidogrel) on plasma level of inflammatory markers in type 2 diabetes mellitus (T2DM) patients with high platelet reactivity (HPR (Cardiol J 2013; 20, 5: 545-551)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
2
24
0
1
Order By: Relevance
“…Switching aspirin (75 mg·day −1 ) to clopidogrel (75mg·day −1 ) reduced the concentrations of some inflammatory markers (in particular high sensitive C reactive protein (hsCRP), IL‐6 and CD40L) in diabetic patients with remaining high platelet reactivity (Rosiak et al, ). In contrast, in patients with coronary heart disease (CHD), no between‐group differences in circulating markers of inflammation after 1 year treatment with clopidogrel (75 mg·day −1 ) compared with aspirin (160 mg·day −1 ) was evident, but both treatments reduced the levels of TNF‐α (Solheim et al, ).…”
Section: Effects On Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Switching aspirin (75 mg·day −1 ) to clopidogrel (75mg·day −1 ) reduced the concentrations of some inflammatory markers (in particular high sensitive C reactive protein (hsCRP), IL‐6 and CD40L) in diabetic patients with remaining high platelet reactivity (Rosiak et al, ). In contrast, in patients with coronary heart disease (CHD), no between‐group differences in circulating markers of inflammation after 1 year treatment with clopidogrel (75 mg·day −1 ) compared with aspirin (160 mg·day −1 ) was evident, but both treatments reduced the levels of TNF‐α (Solheim et al, ).…”
Section: Effects On Inflammationmentioning
confidence: 99%
“…Interestingly, the anti-inflammatory actions of the active metabolite of prasugrel was likely derived from direct targeting of neutrophils isolated from human blood and was P2Y 12 receptor independent (Liverani et al, 2013). This has been recently reviewed by Thomas and Storey (2015. Switching aspirin (75 mg·day À1 ) to clopidogrel (75mg·day À1 ) reduced the concentrations of some inflammatory markers (in particular high sensitive C reactive protein (hsCRP), IL-6 and CD40L) in diabetic patients with remaining high platelet reactivity (Rosiak et al, 2013). In contrast, in patients with coronary heart disease (CHD), no betweengroup differences in circulating markers of inflammation after 1 year treatment with clopidogrel (75 mg·day À1 ) compared with aspirin (160 mg·day À1 ) was evident, but both treatments reduced the levels of TNF-α (Solheim et al, 2006).…”
Section: Thienopyridinesmentioning
confidence: 99%
“…One of the potential explanations is that in the analysis we included only baseline measurement of platelet reactivity. It has been reported that platelet hyperactivity could change not only during a day but also in long-term observation; hence, our results may not represent possible changes of platelet reactivity over time related to biochemical and metabolic disturbances [2, 9, 32, 33, 3540]. …”
Section: Discussionmentioning
confidence: 70%
“…In addition, platelet hyperactivity can be explained by reduced sensitivity to agents exerting an inhibitory modulation of platelet responses, altered intracellular milieu with elevated cytosolic Ca2+, intensified thromboxane A2 synthesis and an increased number and function of GPIIb/IIIa complexes on platelet membranes [31]. In our previous studies, we also found that in some diabetic patients reactivity can be increased despite ASA therapy and modulated by both clinical and biochemical variables [2, 9, 32, 33]. However, in the current investigation we failed to find any association between platelet function and long-term cardiovascular events prognosis [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the Aspirin Versus/Or Clopidogrel in Aspirin-resistant Diabetics inflammation Outcomes (AVOCADO) study in patients with coronary artery disease and diabetes type 2, clopidogrel was found to reduce high-sensivity CRP and CD40 ligand, responsible for the activation of multiple inflammatory processes involved in atherogenesis and ACS [43]. On the other hand, Ramadan et al [44] showed in a 6-week prospective, randomised, placebo-controlled study that apart from a significant CD40 ligand level reduction, clopidogrel did not affect other inflammation markers, endothelial status, and parameters of oxidative stress.…”
Section: Antiplatelet Agentsmentioning
confidence: 99%